Cadmium in Paddy Soil and Rice Crop in Indonesian Intensive Farming System - Budianta, Dedik; Suarji, Muhammad Agung; Napoleon, A; Suntoro, Suntoro; Santoso, Joko; Bolan, Nanthi (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2023)
Agriculture serves as a critical sector underpinning the livelihood of the Indonesian population.. Thus the implementation of this sector involves the use of fertilizers as inputs. However, A prevalent misconception among farmers is that increased fertilization invariably leads to enhanced yield. Excessive fertilization using inorganic compounds, such as phosphorous (P) can elevate levels of Cadmium (Cd), which is a potentially toxic metal for the environment and humans. Therefore, this study aimed to investigate the concentration of the heavy metal cadmium (Cd) in both soil and rice plants in Marga Cinta, Belitang Madang Raya District, East Ogan Komering Ulu Regency, South Sumatra, Indonesia. The method involved a comprehensive survey approach and spanned across 96-hectares of paddy fields, which were divided into six distinct locations. Each location comprised 16 hectares of rice fields, with five sample points drilled to a depth of 0-30 cm. The results showed that the content of Cd in paddy soil and rice plants had exceeded national food safety standards. Hence, farmers were advised to balance their use of phosphorus-rich fertilizers with organic ones, mitigating the rise in soil Cd content. This balance necessitates a reduction in the usage of other chemical fertilizers, favoring organic fertilization methods to promote phytoremediation